Good-vs. poor-trial feedback in motor learning: The role of self-efficacy and intrinsic motivation across levels of task difficulty. (June 2018) - Abbas, Z.A.; North, J.S.
Abstract: In this study we examined the effects of feedback (knowledge of results; KR) after good and poor performances on self-efficacy and intrinsic motivation when learning easy and more difficult motor tasks. Participants were assigned to a KR-good, KR-poor, or KR-neutral (control) condition where they putted a golf ball to a target hole at distances of 2m (easy) and 5m (more difficult). All participants received KR on three trials in each six-trial block. Measures of self-efficacy and intrinsic motivation were taken after each test phase; and learning was inferred from 24-h and one-week retention tests. The KR-good group showed the highest levels of self-efficacy and intrinsic motivation, relative to the other two feedback groups, and more accurate putting performance. These effects persisted after one week and were more pronounced for the more difficult task. There is evidence for the motivational effects of feedback on motor learning, which has implications for theory and practice. Highlights: Evidence for a motivational effect of feedback on motor learning is presented. Self-efficacy was higher for feedback given after more versus less accurate trials. Higher intrinsic motivation was also shown, as well as better task performance. These effects generalise to the learning of both simple and more difficult tasks.